Optimizing enteral nutrition delivery by implementing volume-based feeding protocol for critically ill patients: an updated meta-analysis and systematic review - Lu Wang; Yu Wang; Hua-Xin Li; Rui-peng Zhang; Li Chang; Jun Zeng; Hua Jiang (Critical Care, 2023)
Abstract Background This study aims to provide an updated assessment of the efficacy of optimized enteral nutrition (EN) delivery by implementing the volume-based feeding (VBF) protocol in critically ill patients. Methods We updated our previous literature retrieval with no language restrictions. The inclusion criteria were:1) Participants: Critically ill patients (Patients who was admitted in ICU; 2) Intervention: The VBF protocol was adopted for EN administration; 3) Comparison: The rate-based feeding (RBF) protocol was adopted for EN administration; 4) Major outcomes: EN nutrition delivery. The exclusion criteria included participants aged < 18 years, duplicated literature, animal and cellular experiments, and studies lacking any of the outcomes mentioned in the inclusion criteria. The databases included MEDLINE (through PubMed), Web of Science, Cochrane Library, Chinese Biomedical Literature Service System (SinoMed), Wanfang Data Knowledge Service Platform, and China National Knowledge Infrastructure. Result Sixteen studies involving a total of 2896 critically ill patients are included in the updated meta-analysis. Compared with the previous meta-analysis, nine new studies were added that included 2205 more patients. The VBF protocol significantly improved energy (MD = 15.41%, 95% CI: [10.68, 20.14], p < 0.00001) and protein (MD = 22.05%, 95% CI: [10.89, 33.22], p = 0.0001) delivery. The patients in the VBF group stayed in the ICU for a shorter time (MD = 0.78, 95% CI: [0.01, 1.56], p = 0.05). The VBF protocol did not increase the risk of death (RR = 1.03, 95% CI: [0.85, 1.24], p = 0.76) or prolong the mechanical ventilation duration (MD = 0.81, 95% CI: [-0.30,1.92], p = 0.15). In addition, the VBF protocol did not affect EN complications, such as diarrhea (RR = 0.91, 95% CI: [0.73, 1.15], p = 0.43), emesis (RR = 1.23, 95% CI: [0.76, 1.99], p = 0.41), feeding intolerance (RR = 1.14, 95% CI: [0.63, 2.09], p = 0.66), and gastric retention (RR = 0.45, 95% CI: [0.16, 1.30], p = 0.14). Conclusion Our study revealed that the VBF protocol significantly improved calorie and protein delivery in critically ill patients with no additional risk.